Orbital Hydatid Disease: A case study of young patients with primary orbital lesion - Alhemiarya, Hayder A . (AL-Kindy College Medical Journal, 2014)
Background:This is a prospective study of three children presented to us in the Orbital clinic in AL ShahidGazi Al Hariri Hospital with painless proptosiswith suspension of Hydatid disease.Objectives: : Orbital hydatid disease is a rare lesion accounting for less than 1% of the total lesions of the body (1, 2). Orbital cysts presented as a primary lesion in our study which is rare to have such lesion without involvement of other organs (3). Humans represent the intermediate host where the commonly affected organ are liver and the lung (10-15%) (4). Methods:This is a prospective study of three Children presented to us in the Orbital clinic in Al Shahid Ghazi Alhariri Hospital with painless proptosis with suspension of Hydatid disease, depending on the cultural background and baseline investigation done elsewhere, during the period from Jan. 2012 to Jan. 2013.Results:Three children presented to us with painless proptosis one of them involving the right eyewhile the other two involve the left eye. One of patients male aged only three years while the other two were females aged nine and thirteen years of age. After radiological investigations two of the Children found to have a cystic extraconal lesion in superolateral angle of the orbit while the other one his lesions found in the superomedial angle of the orbit. The first two surgically approached by lateral orbitotomy while the other one by medial orbitotomy trying to avoid rupture of the cysts. After histopathological investigation of the lesions the diagnosis was confirmedasHydatidcyst.conclusions:Hydatid cyst of the Orbit is uncommon disease account for less than 1% of the total orbital lesions of the body.Haydatid disease of the orbit more common on the left side.The most common sites involved in the Orbit are the superolateral and superomedialangle.Haydatid disease of the orbit can present as a primary lesion without evidence of involvement of other part of the body.Haydatid disease of the orbit can present below 7 years of age.Haydatid cyst of the orbit can be removed intact with meticulous dissection